Edible films from polyneric blends of chitosan, pectin and cassava starch - Costa, Tamara Lorena; Leite, Ricardo Henrique Lima; Aroucha, Edna Maria Mendes; Santos, Francisco Klebson Gomes (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
Non-biodegradable polymeric materials have become a problem due to their long degradation time in the environment. Thus, studies show interest in the development of polymeric films and mixtures of these as functional materials in the most diverse areas, especially due to their characteristics such as biocompatibility, biodegradability and non-toxicity. Therefore, the objective was to develop and characterize edible films produced by polymeric blends, composed of natural polysaccharides, aiming at their use as edible coatings for fruits. Seven polymeric films were developed using the casting technique: film 1 (Chitosan), film 2 (Pectin), film 3 (Cassava Starch), film 4 (Chitosan + Pectin), film 5 (Chitosan + Cassava Starch), film 6 (Pectin + Cassava Starch) and film 7 (Chitosan + Pectin + Cassava Starch). All presented homogeneous surfaces and without phase separation. Regarding optical properties, all obtained high luminosity, the most opaque being those of chitosan, presenting L * 77.40 ± 0.28 (4). Regarding the barrier properties, the solubility values were lower in those containing chitosan due to their insolubility in water, 22% for 1 and 18% for 5. The films formed by the blends provided a reduction in the water permeation rate without compromise its characteristics, such as 4 and 5, with a rate of 14.15 g.m-2.h-1 and 20.43 g.m-2.h-1, respectively.